Carbonyl complexes of copper(i) stabilized by bridging fluorinated pyrazolates and halide ions. Issue 19 (1st April 2019) - Parasar, Devaborniny; Jayaratna, Naleen B.; Muñoz-Castro, Alvaro; Conway, Allison E.; Mykhailiuk, Pavel K.; Dias, H. V. Rasika
Abstract : Halide ions provide a promising tool to stabilize – through bridging interactions – copper carbonyl clusters of fluorinated pyrazolates. Abstract : Syntheses of neutral and anionic, di- and tetra-nuclear copper carbon monoxide complexes using binary copper(i ) pyrazolate precursors are reported. The reaction of {[3, 5-(CF3 )2 Pz]Cu}3 (2 ), {[4-Cl-3, 5-(CF3 )2 Pz]Cu}3 (3 ) or {[3, 4, 5-(CF3 )3 Pz]Cu}3 (4 ) with CO in CH2 Cl2 led to copper carbonyl complexes. They however, lose CO quite easily if not kept under a CO atmosphere. Compounds {[3, 5-(CF3 )2 Pz]Cu(CO)}2 (5 ) and {[3, 4, 5-(CF3 )3 Pz]Cu(CO)}2 (7 ) were characterized by X-ray crystallography. They are dinuclear species with a Cu2 N4 core. The reaction of {[3, 5-(CF3 )2 Pz]Cu}3 with CO in the presence of [NEt4 ]Br or [NEt4 ][3, 5-(CF3 )2 Pz] affords relatively more stable [NEt4 ][{[3, 5-(CF3 )2 Pz]Cu(CO)}4 (μ4 -Br)] (8 ) and [NEt4 ]{[3, 5-(CF3 )2 Pz]3 Cu2 (CO)2 } (9 ). The related [NEt4 ][{[4-Cl-3, 5-(CF3 )2 Pz]Cu(CO)}4 (μ4 -Br)] (10 ) and [NEt4 ][{[4-Cl-3, 5-(CF3 )2 Pz]Cu(CO)}4 (μ4 -Cl)] (11 ) can be synthesized using {[4-Cl-3, 5-(CF3 )2 Pz]Cu}3, CO and [NEt4 ]Br or [NEt4 ]Cl. The X-ray structures show that8, 10 and11 are tetranuclear species with terminal Cu–CO groups and quadruply bridging Cl − and Br − ions. Compound9 features an anionic cage of nearly D 3h symmetry formed by three bridging [3, 5-(CF3 )2 Pz] − ions and two terminal Cu–CO moieties. Theoretical calculations show that bonding in these 16- and 18-electron copper complexes follows Dewar–Chatt–Duncanson (DCD) model, where the CO stretching frequencies correlate well to the orbital interaction energy Δ E orb . The major Cu–CO interaction however is electrostatic in nature. Further theoretical exploration of the role of the substituent at pyrazolyl ring 4-position between –H, –Cl, and –CF3, shows a slight decrease in covalent character of the Cu–CO interaction and diminished π-back bonding as pyrazolate groups become more weakly donating with added electron withdrawing substituents.